RISK FACTORS AFFECTING URIC ACID LEVELS IN HYPERURISEMIA PATIENTS - nunung sri mulyani (Poltekkes Kemenkes Semarang, 2022)
Background : The causes of hyperuricemia are divided into 2, namely factors that cannot be controlled and those that can be controlled. Factors that cannot be controlled are age, sex and genetics, while factors that can be controlled are BMI and purine intake. The purpose of this study was to determine the risk factors that affect uric acid levels in hyperuricemia patients in the Muara Satu Health Center Work Area, Lhokseumawe City.Methods : This research is descriptive analytic usingdesign case control. This research was carried out at the Muara Satu Health Center, Lhokseumawe City in February 2021. Age, sex and genetic data were collected using a questionnaire by means of interviews. BMI was collected using weight and TB measurements and purine intake was collected using recall by means of interviews. Data were analyzed using Chi-Squarae . Results : Most of the hyperuricemia patients were in the early elderly as many as 11 people (52.4%) and 18 women (85.7%). BMI mostly mild overweight as many as 14 people (66.7%) and have a genetic history as many as 12 people (57.1%) with purine intake mostly 18 people (85.7%).Conclusion : There is a significant relationship between genetics and purine intake with uric acid levels and there is no significant relationship between age, gender and BMI with uric acid levels in hyperuricemic patients who are outpatients at the Muara Satu Health Center, Lhokseumawe.Suggestion : It is recommended for people with hyperuricemia to pay attention to the intake of food sources of purines, in order to normalize blood uric acid levels. Key words : Age; Gender; Genetics; BMI; Purine intake